Musical hallucinations: review of treatment effects - Coebergh, Jan A. F.; Lauw, R. F.; Bots, R.; Sommer, I. E. C.; Blom, J. D. (Frontiers in Psychology, 2015)
Abstract Background: Despite an increased scientific interest in musical hallucinations throughout the past 25 years, treatment protocols are still lacking. This may well be due to the fact that musical hallucinations have multiple causes, and that published cases are relatively rare. Objective: To review the effects of published treatment methods for musical hallucinations. Methods: A literature search yielded 175 articles discussing a total number of 516 cases, of which 147 articles discussed treatment in 276 individuals. We analysed the treatment results in relation to the aetiological factor considered responsible for the mediation of the musical hallucinations, i.e., idiopathic/hypoacusis, psychiatric disorder, brain lesion and other pathology, epilepsy or intoxication. Results: Musical hallucinations can disappear without intervention. When hallucinations are bearable, patients can be reassured without any other treatment. However, in other patients musical hallucinations are so disturbing that treatment is indicated. Distinct aetiological groups appear to respond differently to treatment. In the hypoacusis group, treating the hearing impairment can yield significant improvement and coping strategies (e.g. more acoustic stimulation) are frequently helpful. Pharmacological treatment methods can also be successful, with antidepressants being more helpful than antiepileptics (which are still better than antipsychotics). The limited use of acetylcholinesterase inhibitors has looked promising. Musical hallucinations occurring as part of a psychiatric disorder tend to respond well to psychopharmacological treatments targeting the underlying disorder. Musical hallucinations experienced in the context of brain injuries and epilepsy tend to respond well to antiepileptics, but their natural course is often benign, irrespective of any pharmacological treatment. When intoxication is the main aetiological factor, it is important to stop or switch the causative substance